2010
DOI: 10.1089/scd.2009.0398
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Reg Family Proteins in Embryonic Stem Cells and Its Modulation by Wnt/β-Catenin Signaling

Abstract: Regenerating islet (Reg) proteins are involved in the proliferation and differentiation of diverse cell types. However, whether embryonic stem cells (ESCs) express Reg genes and their corresponding proteins remains unknown. In this study, we probed the expression of Reg family members by mouse ESCs (mESCs). Mouse Reg1 and Reg3γ were detected in undifferentiated stem cells. Furthermore, we tested if gastrin-an inducer of Reg1 expression in committed cells-up-regulates the Reg1 gene in mESCs. Gastrin did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…As already mentioned, discovery of Reg expression in ESCs was recently reported (90). Considering the key roles of β-catenin/Wnt signaling in stem cell self-renewal and differentiation, we investigated whether a link between canonical Wnt and Reg exists in mESCs, similar to that in various cancer cells.…”
Section: Signaling Pathways and Reg Proteinsmentioning
confidence: 79%
See 1 more Smart Citation
“…As already mentioned, discovery of Reg expression in ESCs was recently reported (90). Considering the key roles of β-catenin/Wnt signaling in stem cell self-renewal and differentiation, we investigated whether a link between canonical Wnt and Reg exists in mESCs, similar to that in various cancer cells.…”
Section: Signaling Pathways and Reg Proteinsmentioning
confidence: 79%
“…The first account of Reg expression in embryonic stem cells (ESCs) was provided by Jing et al (90). When probed for different Reg genes, mouse ESCs (mESCs) showed expression of Reg1 and Reg3γ under non-differentiating conditions.…”
Section: Reg Proteins In Extrapancreatic Tissues and Cellsmentioning
confidence: 99%
“…CatL stimulates REG expression through inhibition of Ecadherin and activation of β-catenin signalling E-cadherin, which is expressed in pancreatic islets [18,19], has been shown to inhibit signalling by sequestering β-catenin [20]. Increased levels of E-cadherin during islet formation mediate a decline in the rate of beta cell proliferation [21] and REG upregulation has been linked to the activation of β-catenin [22,23]. We therefore hypothesised that the functional crosstalk between pancreatic ductal epithelium and beta cell proliferation may involve CatL-mediated activation of the Ecadherin-β-catenin pathway.…”
Section: Reg Proteins Mediate Beta Cell Proliferation In Response To mentioning
confidence: 99%
“…Later, the same protein was independently cloned and sequenced from regenerating pancreatic islets (13). Analysis has revealed that PSP is expressed in various cell types in the gastrointestinal tract (14). During inflammation, PSP is up-regulated in the pancreas, the small intestine, and the stomach.…”
mentioning
confidence: 99%